Quadratic Equations 2x²-5x-3=0Pls Answer Fast Then Only I Will Mark Brainlest Answer Will Be Right About the author Everleigh

Answer: Step-by-step explanation: Here, we have ⇒ 2x² – 5x + 3 = 0 Dividing equation by 2, we get ⇒ x² – 5/2x + 3/2 = 0 Shifting the constant term on RHS ⇒ x² – 5/2x = – 3/2 Adding (1/2 coefficient of x)² on both sides ⇒ (x – 5/4)² = 25/16 – 3/2 ⇒ (x – 5/2)² = 1/16 ⇒ x – 5/4 = ± 1/4 or x = 5/4 – 1/4 = 4/4 ⇒ x = 3/2, 1 Hence, the roots of the equation 2x² – 5x + 3 = 0 are 3/2 and 1. Reply

Answer: [tex]2x {}^{2} – 6x + x – 3 \\ 2x(x – 3) + 1(x – 3) \\ (2x + 1)(x – 3)[/tex] Hence zeroes are = 3,-1/2 Reply

Answer:Step-by-step explanation:Here, we have

⇒ 2x² – 5x + 3 = 0

Dividing equation by 2, we get

⇒ x² – 5/2x + 3/2 = 0

Shifting the constant term on RHS

⇒ x² – 5/2x = – 3/2

Adding (1/2 coefficient of x)² on both sides

⇒ (x – 5/4)² = 25/16 – 3/2

⇒ (x – 5/2)² = 1/16

⇒ x – 5/4 = ± 1/4 or x = 5/4 – 1/4 = 4/4

⇒ x = 3/2, 1

Hence, the roots of the equation 2x² – 5x + 3 = 0 are 3/2 and 1.

Answer:[tex]2x {}^{2} – 6x + x – 3 \\ 2x(x – 3) + 1(x – 3) \\ (2x + 1)(x – 3)[/tex]

Hence zeroes are = 3,-1/2